Dyadic Profiles of Couples Coping With Body Image Concerns After Breast Cancer: Preliminary Results of a Cluster Analysis - Saita, Emanuela; Ferraris, Giulia; Acquati, Chiara; Molgora, Sara; Sorge, Antonia; Valenti, Francesco; Grassi, Massimo Maria; Vagnini, Denise (Frontiers in Psychology, 2022)
Breast cancer treatments have multiple adverse effects, including concerns about body appearance and function that are experienced by most patients. Altered body image negatively affects mental health, social, and relationship functioning. While the relationship with a partner is critical for patients’ psychological wellbeing and partners can promote positive body image, limited research has investigated individual and relational factors affecting the experience of both. This cross-sectional study aimed at (1)exploring rates of body image concerns among breast cancer patients, and (2)identifying dyadic profiles among participating dyads. Couples composed by patients who had undergone surgery and their romantic partners (n=32) were recruited from the Breast Unit of a hospital in northern Italy. Both partners completed measures of personality characteristics (BFQ-2), psychological distress (HADS), coping flexibility (PACT), dyadic coping (DCQ), and closeness (IOS). Body image (BIS) and adjustment to cancer (Mini-MAC) measures were completed by patients only. K-mean cluster analyses identified 2-cluster solution among patients and partners, respectively. “Active patients” (cluster-1) reported low rates of body image concerns (p<0.001), anxious preoccupation, negative dyadic coping, and self-oriented stress communication (p<0.05), compared to “worried patients” (cluster-2). “Comfortable partners” (cluster-1) reported lower anxiety and depression (p<0.001), self-oriented negative dyadic coping and closeness (p<0.05) than “uncomfortable partners” (cluster-2). Three different dyadic profiles emerged: functional, dysfunctional, and ambivalent. Significant variations (p<0.05) by anxiety, depression, and delegating dyadic coping existed. Results indicate there are groups of couples at greater risk for impaired psychological distress and body image concerns, which should be addressed in the context of dyadic psychosocial interventions.